Bie-Jia-Ruan-Mai-Tang, a Chinese Medicine Formula, Inhibits Retinal Neovascularization in Diabetic Mice Through Inducing the Apoptosis of Retinal Vascular Endothelial Cells - Liu, Qiu-Ping; Chen, Yu-Ying; Yu, Yuan-Yuan; An, Pei; Xing, Yi-Zhuo; Yang, Hong-Xuan; Zhang, Yin-Jian; Rahman, Khalid; Zhang, Lei; Luan, Xin; Zhang, Hong (Frontiers in Cardiovascular Medicine, 2022)
Proliferative diabetic retinopathy (PDR) is one of the main complications of diabetes, mainly caused by the aberrant proliferation of retinal vascular endothelial cells and the formation of new blood vessels. Traditional Chinese medicines possess great potential in the prevention and treatment of PDR. Bie-Jia-Ruan-Mai-Tang (BJ), a Chinese medicine formula, has a good therapeutic effect on PDR clinically; however, the mechanism of action involved remains unclear. Therefore, we investigated the effect of BJ on PDR through in vitro and in vivo experiments. A diabetic mouse model with PDR was established by feeding a high-fat–high-glucose diet combined with an intraperitoneal injection of streptozotocin (STZ), while high-glucose-exposed human retinal capillary endothelial cells (HRCECs) were employed to mimic PDR in vitro. The in vivo experiments indicated that BJ inhibited the formation of acellular capillaries, decreased the expression of VEGF, and increased the level of ZO-1 in diabetic mice retina. In vitro experiments showed that high glucose significantly promoted cell viability and proliferation. However, BJ inhibited cell proliferation by cycle arrest in the S phase, thus leading to apoptosis; it also increased the production of ROS, decreased the mitochondrial membrane potential, reduced the ATP production, and also reduced the expressions of p-PI3K, p-AKT, and Bcl-xL, but increased the expressions of Bax and p-NF-κB. These results suggest that BJ induces the apoptosis of HRCECs exposed to high glucose through activating the mitochondrial death pathway by decreasing the PI3K/AKT signaling and increasing the NF-κB signaling to inhibit the formation of acellular capillaries in the retina, thus impeding the development of PDR.